2012
DOI: 10.2337/db10-1492
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cell Cotransplantation Enhances Islet Engraftment by Rapid Revascularization

Abstract: Impaired revascularization of transplanted islets is a critical problem that leads to progressive islet loss. Since endothelial progenitor cells (EPCs) are known to aid neovascularization, we aimed to enhance islet engraftment by cotransplanting EPCs with islets. Porcine islets, with (islet-EPC group) or without (islet-only group) human cord blood–derived EPCs, were transplanted into diabetic nude mice. The islet-EPC group reached euglycemia by ∼11 days posttransplantation, whereas the islet-only group did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 50 publications
5
74
0
1
Order By: Relevance
“…Interestingly, while the proliferative capacity of beta cells has been questioned for many years, recent lineage-tracing studies have revealed the remarkable capacity of adult beta cells to support beta cell mass maintenance and regeneration through replication [19][20][21]. Our data underscore the potential of beta cells to replicate in an islet-transplantation setting and are in line with a beneficial effect of co-transplantation of EPC on the replication rate of the engrafted beta cells [8]. Unlike Kang et al [8], the current report shows the effect of adult human outgrowth endothelial cells with autologous potential rather than the effect of cord-blood-derived EPC.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Interestingly, while the proliferative capacity of beta cells has been questioned for many years, recent lineage-tracing studies have revealed the remarkable capacity of adult beta cells to support beta cell mass maintenance and regeneration through replication [19][20][21]. Our data underscore the potential of beta cells to replicate in an islet-transplantation setting and are in line with a beneficial effect of co-transplantation of EPC on the replication rate of the engrafted beta cells [8]. Unlike Kang et al [8], the current report shows the effect of adult human outgrowth endothelial cells with autologous potential rather than the effect of cord-blood-derived EPC.…”
Section: Discussionsupporting
confidence: 68%
“…Previous reports have shown that endothelial (progenitor) cells of different origin can improve transplanted beta cell survival and function [7,8,16]. Nevertheless, in contrast to these studies, which evaluated the effect of non-human and/or human cord-blood-derived cells, the present study pioneers co-transplantation of adult human peripheral BOEC with a marginal-islet graft and reports a significant BOEC-specific increase in plasma C-peptide levels and improvement in blood glucose control.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although we cannot exclude that the observed improvement in blood glucose control and increased insulin content is due to an increased insulin content per cell, our previous report 4 illustrated that BOEC co-engraftment resulted in an increased β-cell volume via a reduction in β-cell death and stimulation of β-cell proliferation. While others have reported that endothelial (progenitor) cells of different origins can improve survival and function of transplanted islets, [16][17][18] our study is, to our knowledge, the first to illustrate the beneficial effect on islet transplantation of adult, human, peripheral blood derived endothelial cells. As we were previously able to mimic the observed beneficial glycometabolic effect with BOEC derived from a type 1 diabetic individual, 4 we further confirmed the autologous transplantation potential of BOEC.…”
Section: Discussionmentioning
confidence: 60%
“…As we were previously able to mimic the observed beneficial glycometabolic effect with BOEC derived from a type 1 diabetic individual, 4 we further confirmed the autologous transplantation potential of BOEC. Moreover, while some research groups reported an effect of endothelial (progenitor) cells on rapid graft revascularization, 17 BOEC co-engraftment did not affect islet vessel density but rather resulted in an increased graft-vessel and β-cell volume at day 28 PTx. Although we cannot exclude that BOEC, like other primary human endothelial cells, 16 do have a potential benefit on IBMIR-related islet damage, our previous and current report illustrates that BOEC provide other, presumably trophic, support to promote the outcome of islet transplantation and subsequently reverse hyperglycemia.…”
Section: Discussionmentioning
confidence: 90%